Mattering as a Political, Scientific, and Professional Basis for Welfare Services - Krokstad, Steinar (Frontiers in Psychology, 2021)
The dominant political ideology of recent decades, neoliberalism, have resulted in diminished sense of mattering for several groups in the society, not at least people outside the labor market. This has left its mark on vocational rehabilitation programs in welfare states like Norway. Higher requirements shall be set for benefit recipients, and compulsory work are more often applied. The problem with this policy is that it suggests that benefit recipients have a guilt to make up for and are themselves to blame for the unemployment. However, the majority of people in need for vocational rehabilitation, have had poor living conditions since childhood, and have failed in education and employment for or reasons they have no control over. They often do not feel valued and have a lot of experience with not being able to add value. The problem with blaming the victims, is that it reinforces their sense of worthlessness, and thus reduces their ability to believe that they can contribute with something of value. In this way, the policy becomes counterproductive. Some even respond to these humiliating pressures by becoming more depressive or aggressive. To make vocational rehabilitation programs effective, we must make sure that everyone in need for it feel valued, we must align the political, scientific, and professional basis for welfare service politics thereafter. We must balance adding value to self with the opportunity to adding value to others, work and community. Mattering is suggested as a political, scientific, and professional basis for welfare services.